Seapower a guide for the twenty-first century - Till, Geoffrey (Routledge, 2009)
The sea has always been central to human development as a source of resources, and as a means of transportation, information-exchange and strategic dominion. It has been the basis for our prosperity and security. This is a guide for students of naval history and maritime strategy, and those interested in the role of seapower in the 21st century.